Technology optimization and change management for successful digital supply chains - Sabri, Ehap H., 1967- (Advances in logistics, operations, and management science (ALOMS) book series., 2019)
"This book provides a guide to the best practices in digital enablement, change management, and process optimization. It also builds on the available limited literature in the field of digital supply chain optimization and business transformation and complement it with practical and proven tactics from the industry"--